P214 The prevalence of upper thoracic breathing pattern in patients with breathing pattern disorder and inducible laryngeal obstruction. (12th November 2019) - Harrison, JL; Slinger, R; Wilson, H; Slinger, C
Abstract : Introduction: Patients referred to a Tertiary Airways and Severe Asthma Service for refractory breathlessness may be diagnosed with Breathing Pattern Disorder (BPD) or Inducible Laryngeal Obstruction (Ilo). Both are known to be comorbidities frequently seen in difficult-to-treat asthma (Tay et al, 2016). Ilo and BPD are frequently seen together in clinical practice, however research has not consistently shown overlap between the two conditions (Denton et al, 2019). Aims: To investigate breathing patterns within a sample of patients referred to a tertiary Airways service diagnosed with Ilo, BPD or both. Method: Records of patients with a diagnosis of BPD (identified by a specialist physiotherapist) over a 12 month period (N=56) were reviewed using purposive sampling to identify people with Ilo (diagnosed by laryngoscopy) and those without. Breathing pattern, respiratory rate and Nijmegen questionnaire (NQ) were compared between patients diagnosed with BPD and Ilo and those with BPD alone. Results: The mean respiratory rate of the full sample was 20.09 (SD=5.949), with a mean NQ score of 26.94 (SD=10.33) indicating significant hyperventilation. Of the 56 patients with BPD, 26 were also diagnosed with Ilo. Non-parametric comparisons of means showed no significant differences in mean respiratory rates or NQ scores between patients with and without Ilo. Frequencies of different breathing patterns across groups are shown in Figure 1 below: The most common breathing pattern was upper thoracic (71% of sample). This was found in 85% of patients with Ilo, compared to 60% of patients without Ilo. Conclusions: Patients with a diagnosis of both Ilo and BPD appear to have a greater likelihood of upper thoracic breathing pattern disorder than those with BPD alone. Prevalence of upper thoracic breathing pattern in Ilo is not fully understood. Studies suggest rates for upper thoracic breathing may be up to 86% within breathing pattern disorders (Denton et al 2019) but the relationship between this pattern and Ilo has not been investigated. Further research into the role of upper thoracic breathing pattern with larger samples is indicated.